THE INFLUENCE OF CURRENT STRENGTH ON THE TOUGHNESS OF JOINTS IN THE ELECTRODE ELECTRIC ARC WELDING PROCESS WRAPPED (SMAW) AISI 4340 STEEL - Pratama, Andre; Julian; Supriono (PT Inovasi Pratama Internasional, 2024)
The development of advanced construction technology cannot be separated from welding, as it plays an important role in constructing and repairing metal structures. At present, the construction of metal structures involves a lot of welding elements, especially in the field of good quality design. Based on the background, the problem can be formulated, namely, the effect of current strength on strength of Aisi 4340 steel joints after SMAW welding treatment. The research method used is the impact test method to see the results of the influence of strong currents in steel joints. The results of this study are the value of impact toughness at a current variation of 80 Ampere, the first specimen is 0.56080 J/mm2, the second specimen is 0.54811 J/mm2, and the third is 0.51724 J/mm2. The impact toughness value at 95 amps variation of the first sample is 0.01869 J/mm2, the second is 0.05481 J/mm2, and the third is 0.05172 J/mm2. From the test data, it can be seen that the average value of the average impact toughness in the variation of current strength of 80 Ampere and 95 Ampere is 80 Ampere current average impact toughness value of 0.54205 J/mm2 and 95 Ampere current average impact toughness value of 0.04174 J/m2. That the 80 ampere current variation is better and more efficient because it produces a higher toughness value than the 95 ampere current variation.